Hydrocarbon accumulation history in Lower Cretaceous in northern slope of Bongor Basin in Chad, Central Africa - Li WANG; Zhiquan NIE; Yebo DU; Lin WANG; Fanchao MENG; Yuliu CHEN; Jie HU; Ruxin DING (Petroleum Exploration and Development, 2024)
Based on the analysis of the fluid inclusion homogenization temperature and apatite fission track on the northern slope zone of the Bongor Basin in Chad, this paper studied the time and stages of hydrocarbon accumulation in the study area. The results show that: (1) The brine inclusions of the samples from the Kubla and Prosopis formations in the Lower Cretaceous coexisting with the hydrocarbon generally present two sets of peak ranges of homogenization temperature, with the peak ranges of low temperature and high temperature being 75–105 °C and 115–135 °C, respectively; (2) The samples from the Kubla and Prosopis formations have experienced five tectonic evolution stages, i.e., rapid subsidence in the Early Cretaceous, tectonic inversion in the Late Cretaceous, small subsidence in the Paleogene, uplift at the turn of the Paleogene and Neogene, and subsidence since the Miocene, in which the denudation thickness of the Late Cretaceous and after the turn of the Paleogene and Neogene are ~1.8 km and ~0.5 km, respectively. The cumulative denudation thickness of the two periods is about 2.3 km; (3) Using the brine inclusion homogenization temperature coexisting with the hydrocarbon as the capture temperature of the hydrocarbon, and combining with the apatite fission track thermal history modeling, the result shows that the Kubla and Prosopis formations in the Lower Cretaceous on the northern slope of the Bongor Basin have the same hydrocarbon accumulation time and stages, both of which have undergone two stages of hydrocarbon charging at 80–95 Ma and 65–80 Ma. The first stage of charging corresponds to the initial migration of hydrocarbon at the end of the Early Cretaceous rapid sedimentation, while the second stage of charging is in the stage of intense tectonic inversion in the Late Cretaceous.